National and Cultural Identity of the Ukrainian Society in the Context of Modern Humanitarian Challenges - Oksana Semenova; Maryna Herasko (Українознавство, 2020)
Based on the individual questionnaire survey and method of involved observation, the article analyzes main factors of national and cultural identification of members of the Ukrainian society and impact of the destructive Russian factor on their national, ethnic, cultural (linguistic and religious) self-identification, and transformation of their value and worldview orientations as well. The research discovers that humanitarian expansion of the Russian Federation has led to the crisis of national and cultural identity of inhabitants of some territories of Donetsk and Luhansk regions that may cause threat to state sovereignty and territorial integrity, spread of anti-Ukrainian and separatist sentiments, cultural and political disorientation. The survey demonstrates the priority of political and family identities in the respondents’ system of identities. The paper analyzes factors of consolidation of the Ukrainian society, impact of the war in Donbas on national self-consciousness and self-identification of the respondents. The authors show the difference between ethnic self-identification and linguistic behavior of the respondents. It is revealed that Russian-speaking respondents from southeastern Ukraine fell under the influence of Russian and Soviet historical narratives. The authors describe social atmosphere in Kostiantynivka, Donetsk region, before, during, and after occupation by separatist forces of the so-called “DNR”. In particular, they show that the respondents were not eager to answer the questions, avoided detailed answers, or ignored some “uncomfortable” questions. That is why the authors used such additional sources of information as personal observation, and materials of websites and social media platforms devoted to Kostiantynivka.